Optimal Terms of Surgical Treatment of Adhesive Capsulitis (Retrospective Study) - Strafun, S.S.; Strafun, O.S.; Bohdan, S.V.; Yuriichuk, L.M. (TERRA ORTHOPAEDICA, 2022)
Summary. Relevance. Surgical treatment of adhesive capsulitis is infrequent, as the doctor is convinced that this pathology has a staged course and the ’thawing stage’ is inevitable in 12-24 months. Unfortunately, this is not always the case. Objective: to determine the optimal timing for surgical treatment of adhesive capsulitis. Materials and Methods. From 2015 to 2019, we performed 175 arthroscopic surgeries in patients with adhesive capsulitis of the shoulder joint, of which 59 (33.7%) patients were diagnosed with type 2 diabetes. The age of patients ranged from 40 to 70 years. The average age was 55.9±17.2 years. All patients were divided into 2 groups (group 1 – adhesive capsulitis and a history of diabetes, group 2 – adhesive capsulitis). In our study, we retrospectively assessed the function of the shoulder joint on the Constant Shoulder Score and VAS scales before surgery and 12 months after surgery. Results. The surgery performed within 100 days in patients with adhesive capsulitis and diabetes mellitus (group 1) when evaluated on the Constant Shoulder Score demonstrates worse results than the surgery performed at a later date (r=0.6; p<0.05); similar results were obtained on the VAS scale (r=0.62; p<0.05). The surgery performed within 100 days in patients with adhesive capsulitis (group 2) shows worse results on the Constant Shoulder Score than the surgery performed at a later date (r=0.775; p<0.05); similar results were obtained on the VAS scale (r=0.57; p<0.05). There is a tendency of less effective results of treatment on the Constant Shoulder Score and the VAS scale in patients of group 2 when performing surgery more than 350 days after the onset of the disease. Conclusions. Despite a number of conservative methods of treatment of adhesive capsulitis, timely surgery allows to obtain good treatment results. The optimal period for surgical intervention in adhesive capsulitis ranges from 100 to 350 days from the onset of the disease.